2018
DOI: 10.1111/apa.14481
|View full text |Cite
|
Sign up to set email alerts
|

Association between the frequency of bedwetting and late preterm birth in children aged ≥5 years

Abstract: This study revealed that LPT/low BW was associated with increased frequency of bedwetting in children. The results suggest that gestational age should be considered when examining patients with severe bedwetting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…However, in our investigation, the LBW did not predispose to daytime incontinence. What is more, the cohort study performed on 614 Japanese children reports no association between LBW and NE . Admittedly, we noticed a statistical difference in the incidence of NE, but NE was more frequently observed in NBW patients than in LBW patients.…”
Section: Discussioncontrasting
confidence: 45%
“…However, in our investigation, the LBW did not predispose to daytime incontinence. What is more, the cohort study performed on 614 Japanese children reports no association between LBW and NE . Admittedly, we noticed a statistical difference in the incidence of NE, but NE was more frequently observed in NBW patients than in LBW patients.…”
Section: Discussioncontrasting
confidence: 45%
“…It is also the first time that our study found that the additive interaction effects of preterm birth with parasomnias could amplify the risk of childhood wheeze/asthma. Existing evidence has reported links between preterm birth and both wheeze/asthma 7 , 50 and parasomnias, 51 but no one has ever examined the role of preterm in the association between parasomnias and asthma. Since sleep develops during fetal life, prematurity is linked to poor sleep quality and later bedtimes in school-aged children, according to a systematic evaluation of nine qualitative cohort studies.…”
Section: Discussionmentioning
confidence: 99%